Answer:
x = -0.5 or -1
Explanation:
Given the quadratic equation;
2x² + 3x + 1 = 0
The standard form of a quadratic equation is ax² + bx + c = 0
Therefore, a = 2, b = 3 and c = 1
Quadratic equation formula is;
Substituting into the equation, we have;
![x = \frac {-3 \; \pm \sqrt {3^(2) - 4*2*1}}{2*2}](https://img.qammunity.org/2022/formulas/mathematics/college/gvswzmg40af18dnzqdsg6ve5dcbvw1n4qg.png)
![x = \frac {-3 \pm \sqrt {9 - 8}}{4}](https://img.qammunity.org/2022/formulas/mathematics/college/twlmlqdozw3mj7knal4zc8x081tvxjpst5.png)
![x = \frac {-3 \pm \sqrt {1}}{4}](https://img.qammunity.org/2022/formulas/mathematics/college/owaa6rf3aam0bxyt372pzi0fp59kb7y3kb.png)
Simplifying further, we have;
![x_(1) = \frac {-3 + 1}{4}](https://img.qammunity.org/2022/formulas/mathematics/college/5906b5gtypyg5s8dodavlki0f92yo1srx5.png)
![x_(1) = \frac {-2}{4}](https://img.qammunity.org/2022/formulas/mathematics/college/qax5266bjx5h353hfidc6ywjtu0uv2ema4.png)
![x_(1) = -0.5](https://img.qammunity.org/2022/formulas/mathematics/college/j6h9r6siyyfigw3mmp4bz4fac18g6qxypb.png)
To find the value of x2;
![x_(2) = \frac {-3 - 1}{4} \\x_(2) = \frac {-4}{4} \\x_(2) = -1](https://img.qammunity.org/2022/formulas/mathematics/college/1kftkozai51m9rwj2ym0ip398hd172gx0d.png)
Therefore, the value of x = -0.5 or -1